PENGEMBANGAN METODOLOGI PERENCANAAN TRANSPORTASI BARANG REGIONAL - Noor Mahmudah; Siti Malkhamah; Danang Parikesit; Sigit Priyanto (Jurnal Transportasi, 2011)
This paper attempts to elaborate the relationship of the economics activities of commodities toward export -specifically the production of goods and services that generate freight transportation. The spatial data of commodities related to the economics’ activities (resources, factories, and outlets), the transportation data(infrastructures, modes, and services), and government regulations, are use in formulating the method for freight transportation planning utilizing intermodality concept, to produce efficient freight movements and to enhance sustainable mobility and economic development in the regional scale.Keywords: economics activities, freight transportation, sustainable mobility.